GAGASAN KONSEPTUAL SUPERVISOR PENDIDIKAN TENTANG PEMBELAJARAN INOVATIF MODEL LINGKUNGAN SEKITAR SEBAGAI SUMBER BELAJAR - SRI RAHAYU (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2022)
One of the learning strategies in accordance with the Pakem approach that allows students to develop creativity, motivation and participation in learning is to use the school environment as a learning resource. Based on initial observations at SDN 2 Kedungjati, Kedungjati District, Grobogan Regency for the 2019/2020 Academic Year, all classroom teachers and field of study teachers rarely and never even use the school environment as a learning resource, this is due to the lack of understanding and ability of teachers to utilize the school environment as a learning resource. learning resources. So far, teachers have mostly used textbooks and teaching aids owned by schools as learning resources to complement classroom learning activities. To overcome this, it is necessary to have group discussions among classroom teachers in the form of KKG (in house training) to discuss the problem of using the school environment as a learning resource. In these discussion activities, teachers can share experiences in utilizing the school environment as a learning resource to achieve optimal learning outcomes. From the results of the school action research carried out, it can be seen that to improve the ability of teachers to utilize the school environment as a learning resource through a teacher working group (KKG) discussion approach at SDN 2 Kedungjati, Kedungjati District, Grobogan Regency for the 2019/2020 Academic Year. This is evidenced by an increase in student learning outcomes. ABSTRAKSalah satu setrategi pembelajaran yang sesuai dengan pendekatan Pakem yang memungkinkan bisa mengembangkan kreativiats, motivasi dan partisipasi siswa dalam pembelajaran adalah dengan memanfaatkan lingkungan sekolah sebagai sumber belajar. Berdasarkan pengamatan awal di SDN 2 Kedungjati Kecamatan Kedungjati Kabupaten Grobogan Tahun Pelajaran 2019/2020, semua guru kelas dan guru bidang studi jarang dan bahkan tidak pernah memanfaatkan lingkungan sekolah sebagai sumber belajar, hal ini disebabkan oleh kurangnya pemahaman dan kemampuan guru untuk memanfaatkan lingkungan sekolah sebagai sumber belajar.Selama ini guru lebih banyak menggunakan buku paket dan alat peraga yang dimiliki sekolah sebagai sumber belajar untuk melengkapi kegiatan pembelajaran di kelas. Untuk mengatasi hal itu perlu adanya diskusi kelompok diantara para guru kelas dalam bentuk KKG ( in house training) untuk mendiskusikan masalah pemanfaatan lingkungan sekolah sebagai sumber belajar. Dalam kegiatan diskusi tersebut para guru bisa membagi pengalaman dalam pemanfaatan lingkungan sekolah sebagai sumber belajar untuk mencapai hasil belajar yang optimal. Dari hasil penelitian Tindakan sekolah yang dilakukan dapat diperoleh hasil bahwa Untuk meningkatkan kemampuan guru dalam memanfaatkan lingkungan sekolah sebagai sumber belajar melalui pendekatan diskusi kelompok kerja guru (KKG) di SDN 2 Kedungjati Kecamatan Kedungjati Kabupaten Grobogan Tahun Pelajaran 2019/2020 dapat terwujud. Hal ini dibuktikan dengan adanya peningkatan hasil belajar siswa.